Adubação corretiva de fósforo sobre o desempenho de variedades de cana-de-açúcar cultivadas em ambiente restritivo de cerrado - Teixeira, Edson Belisário [UNESP] (2014)
The culture of sugar cane has been highlighted in the savanna of the Brazilian Midwest region, especially in areas occupied by degraded pastures. The growing of sugar cane at these sites implies seeking varieties that are best suited to these new environments that predominate soils with very low levels of phosphorus. Thus, the corrective phosphate may be a promising technology. The experiment was conducted in a Oxisol Alic, coordinates 51º15’00 W and 20º12’57 S, in Aparecida do Taboado city south Mato Grosso state, the objective this research was to evaluate the performance of varieties of sugar cane according to corrective doses of P2O5 fertilization with superphosphate. The design was randomized blocks with split plots, three treatments in plots with phosphorus levels: 150, 300 and 450 kg ha-1 P2O5, and the subplots was the varieties: RB867515, RB855035, SP84-1431, SP83-2847, RB72454, SP81-3250, SP79-1011, RB835486, IACSP93-6006 and IAC91-5155. The experiment was conducted for four cycles in which we evaluated the characteristics agroindustrial of sugar cane. It was concluded that the varieties of cane sugar respond differently to corrective phosphate fertilizer so therefore should be considered in planning the varietal management. Higher doses of corrective phosphate fertilizer increased the sucrose in varieties of early ripening harvested in May, and provided greater yield of stalk in sugar cane